2021
DOI: 10.1017/jfm.2021.323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tabs on transverse jet instabilities, structure, vorticity dynamics and mixing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(52 citation statements)
references
References 51 publications
17
35
0
Order By: Relevance
“…For J = 7 in figure 10(b), the overall best molecular mixing tended to occur for the most active vortex collisions or interactions, especially for vortices with trailing columns, yet it is important to note that pulsewidth as well as pulse spacing contribute to these effects. It is also important to note that forcing conditions which resulted in the best molecular mixing did not usually correspond to conditions of maximum jet penetration, as observed in other forced as well as passively controlled transverse jet experiments [37,38,50]. Importantly, this observation contradicts long held assumptions that improvements in jet penetration correspond to improved molecular mixing [1].…”
Section: Mixing Quantificationmentioning
confidence: 94%
See 2 more Smart Citations
“…For J = 7 in figure 10(b), the overall best molecular mixing tended to occur for the most active vortex collisions or interactions, especially for vortices with trailing columns, yet it is important to note that pulsewidth as well as pulse spacing contribute to these effects. It is also important to note that forcing conditions which resulted in the best molecular mixing did not usually correspond to conditions of maximum jet penetration, as observed in other forced as well as passively controlled transverse jet experiments [37,38,50]. Importantly, this observation contradicts long held assumptions that improvements in jet penetration correspond to improved molecular mixing [1].…”
Section: Mixing Quantificationmentioning
confidence: 94%
“…Each cavity produced light in the IR at 1064 nm, which was then passed through harmonic generators to produce light in the green at 532 nm and the UV at 266 nm, with the latter serving to excite the acetone tracer in the jet. Green laser light is utilized in separate experiments involving particle image velocimetry (PIV) [46,50].Triggering of the laser cavities was possible up to a maximum of 15 Hz, however the internal optics of the laser were optimized for the best UV energy output, and optimal UV to green signal-to-noise ratio (SNR), when operating at 5 Hz. At this operating condition each of the laser cavities was individually capable of producing 8 ns full width at half maximum pulses with UV energy levels of approximately 30-35 mJ.…”
Section: Optical Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the tab is 0.2012D and the base width of the tab is 0.25D, resulting in a 2.3 % geometric blockage of the original circular jet. Note that in the experiments of Harris et al (2021), the nozzle length is extended by 0.19D to accommodate the tab template, which slightly weakened the shear layer compared with the original nozzle. We do not incorporate the same extension into the present simulations to permit direct comparisons with the non-tabbed results of Iyer & Mahesh (2016) and Regan & Mahesh (2017 for the original nozzle.…”
Section: Details Of the Geometry Grid And Computational Domainmentioning
confidence: 99%
“…In contrast, at higher R (corresponding to the naturally CU USL), both the upstream and downstream tabs improved mixing, and the asymmetry of the jet cross-section could be altered through asymmetric placement of the tab, aligning with the increased growth rates of asymmetric modes for R = 4 predicted by Regan & Mahesh (2019) and the sensitivity of these modes to actuation on either side of the upstream edge of the jet exit. Harris et al (2021) suggested that the contrast in USL spectral characteristics and the jet cross-section effects 'might imply greater changes than those actually observed in the jet structure'.…”
Section: Introductionmentioning
confidence: 99%